Menepis Dominasi Gadget, Meraih Berkah Qur'ani: Kisah Sukses Maghrib Mengaji dalam Membangun Karakter dan Literasi Al-Qur'an Generasi Muda Desa Pagaran Gala-Gala - Nur Aisyah Dlt; Salwa Selvia; Royhan Mustofa; Nurul Latifah Sari Pulungan; Nur Aisyah Nst; Rosita Rangkuti; Ildan Saleh; Suaidah Batubara; Nikmah Lubis; M. Khoiruddin Lubis; Rizka Ar-Rahmah (Jurnal Ragam Pengabdian, 2025)
This study aims to describe the effectiveness of the Maghrib Mengaji Program implemented by KKN Group 26 (10 members) in Pagaran Gala-Gala Village in enhancing Qur'anic literacy and fostering religious character. The research utilized a participatory qualitative method with a Case Study approach, where learning activities were conducted intensively at the KKN post after congregational prayers. The program employed the Mutsallasah Curriculum (BTQ, Tahfidz, and Fahmil Qur’an) with the key methodology of direct guidance (talaqqi) by KKN mentors. The findings indicate significant achievements: a marked improvement in participants' reading quality, particularly in Tajwid and Makharijul Huruf, facilitated by the optimal mentor-to-participant ratio. The program also successfully diverted the 'golden time' of Maghrib from non-productive activities (gadgets) to a positive routine, instilling spiritual discipline and responsibility. The program's success was sustained by a strong synergy between the KKN group and mosque officials, which revitalized the institutional role as a center for character education. To ensure sustainability, it is recommended to implement Teacher Regeneration through peer-tutor recruitment and to establish Local Regulations by the village government to make the Maghrib Mengaji Program a continuous and mandatory cultural practice.